1995
DOI: 10.1007/bf00401834
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment in WBN/Kob rats with spontaneous diabetes mellitus

Abstract: SummaryThe inner ear of spontaneously diabetic WBN/Kob rats was functionally and morphologically examined in order to elucidate the relationship between diabetes mellitus and hearing impairment. At 3 months of age, WBN/Kob rats were non-diabetic, and their hearing function was normal. At 6-7 months of age, they showed decreased glucose tolerance and an increasing tendency toward urinary excretion of glucose without high plasma concentration of glucose, and were therefore judged to be pre-diabetic. They also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…This was as expected because the C57BL/6 mice used in the current study are well-known to develop sensorineural hearing loss much earlier in life than other mice (3335). However, no significant differences in aging-related hearing impairment were observed between the diabetic and control mice, in accordance with a previous study using the STZ-induced diabetes model in CBA/CaJ mice (20) but in contrast with findings from the rat model of chronic pancreatitis and spontaneous diabetes (19). Most interestingly, we showed that recovery from noise-induced injury was significantly impaired in an experimental diabetes model, consistent with a previous report using the STZ-induced diabetes rat model (21).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This was as expected because the C57BL/6 mice used in the current study are well-known to develop sensorineural hearing loss much earlier in life than other mice (3335). However, no significant differences in aging-related hearing impairment were observed between the diabetic and control mice, in accordance with a previous study using the STZ-induced diabetes model in CBA/CaJ mice (20) but in contrast with findings from the rat model of chronic pancreatitis and spontaneous diabetes (19). Most interestingly, we showed that recovery from noise-induced injury was significantly impaired in an experimental diabetes model, consistent with a previous report using the STZ-induced diabetes rat model (21).…”
Section: Discussionsupporting
confidence: 91%
“…A longitudinal study on diabetic rats (WBN/Kob) showed hearing impairment compared with age-matched Wistar rats (19). In middle-aged mice, type 2 diabetes induced by a high-fat diet led to significant hearing impairment over a period of 6 months.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 A diabetic condition generated by streptozotocin injection or a high-fat diet also leads to exacerbation of hearing loss in aged mice. 10, 11 In contrast, it has been shown that caloric restriction slows the progression of ARHI in various strains of mice. 12, 13 These data suggest that metabolic dysfunction under conditions of obesity is causally linked to the development of ARHI.…”
mentioning
confidence: 99%